Suasana Hatiku Bagaikan Roller Coaster: Studi Kasus Self-Disclosure di Media Sosial pada Orang dengan Bipolar Semasa Pandemi Covid-19 - Fransiska Uly Simanjuntak; Rudangta Arianti (Kuras Institute, 2022)
This study aims to find out how the description of adolescents with bipolar disorder with drastic and extreme mood changes who carry out self-disclosure on social media during the pandemic. Subject selection using snowball sampling technique. Participants were 2 adolescents with bipolar disorder range aged 18-23 years, using social media for 2-3 hours in one time, and during a pandemic, the number of posts on social media increased, difficult to interact with other people directly and often share posts or writings or things that should not be shared on social media. Retrieval of data in this study using a qualitative approach, using in-depth online interviews, observation and collecting documentation as secondary research data. The results of this study indicate that the subjects experienced drastic changes in living life on social media during the pandemic, both subjects experienced fluctuating emotional changes and both also found ways to express themselves on social media during the pandemic, which states that people with bipolar disorder have lots of topics to talk about and daydream about something out of the ordinary. The main cause of bipolar disorder that often relapses is the pandemic period where people with bipolar disorder often feel relapse because they cannot meet their peers freely and even feel very lonely.